Representaciones sociales de empresarios colombianos, referente a la economía en la fase de posconflicto - José Orlando García-Mendoza; Martha Sofia Orjuela-Abril; Victor Manuel Ardila-Soto (Mundo Fesc)
This research sheds light on the social profiles of business partners in the city of Cúcuta regarding the economy after the conflict. The methodology used was mixed research, engaging in conversations with businesspeople from various sectors in the metropolitan area. The sample was based on the "saturation" criterion, considering the three relational levels: communicative agreement, oral communication, and the social universe of reference. The information was processed using Atlas-ti software, which produced a graphic representation of respondents' perspectives on the economy in the post-conflict era in Colombia, once the country's peace treaties were signed. Likewise, the frequency of repeated phrases was obtained using SPSS, for coding the dimensions found in the data processing. The results present subcategories such as barriers, endogenous development, and investment factors, where multiple dimensions are displayed. In the eyes of businesspeople, a country's economy is dynamic and depends on various factors, including politics, conflict situations, legal factors, and others.